Fostering cyclical convergence in the Euro Area - Gori, Filippo (OECD Publishing, 2021)
During the first decade of the currency union, business cycle fluctuations among Euro Area countries were relatively synchronised and similar in magnitude. This concordance disappeared during the 2008 financial turmoil and the following European sovereign debt crisis, a time when key flaws in the architecture of the euro area became apparent. The recovery helped reduce cross-country differences in unemployment and output gaps, but countries worst hit by the crisis took much longer to recover, and in some cases negative consequences of shocks became entrenched. The COVID-19 crisis could lead to a resurgence in euro area cyclical di-synchronisation, risking to exacerbate economic divergence among member states and putting to the test the macroeconomic stability of the currency union. Diverging cyclical paths among euro area countries originate from differences in economic structures and domestic institutions. However, such differences are compounded by features in the economic policy architecture of the currency union - such as the lack of a common fiscal stabilisation tool - and by remaining frictions in the functioning of the common labour and financial markets. Reforms to the common euro area economic policy framework combined with those to improve labour and capital mobility across euro area members are needed to foster cyclical convergence in the currency union
Keywords: Economics